Lipoprotein-associated phospholipase A(2) and Risk of Dementia in the Cardiovascular Health Study - Fitzpatrick, Annette L. (2014)
OBJECTIVE: To evaluate associations between Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) mass and activity with risk of dementia and its subtypes. METHODS: Analysis were completed on 3,320 participants of the Cardiovascular Health Study (CHS), a population-based longitudinal study of community-dwelling adults age ≥ 65 years followed for an average of 5.4 years. Baseline serum Lp-PLA(2) mass was measured using a sandwich enzyme immunoassay and Lp-PLA(2) activity utilized a tritiated-platelet activating factor activity assay. Cox proportional hazards regression assessed the relative risk of incident dementia with higher baseline Lp-PLA(2) adjusting for demographics, cardiovascular disease (CVD) and risk factors, inflammation markers and apolipoprotein E (APOE) genotype. RESULTS: Each standard deviation higher Lp-PLA(2) mass and activity were related to increased risk of dementia (fully adjusted HR:1.11 per SD, 95% CI:1.00-1.24 for mass; HR:1.12 per SD, 95% CI:1.00-1.26 for activity). Persons in the highest quartile of Lp-PLA(2) mass were 50% more likely to develop dementia than those in the lowest quartile in adjusted models (HR: 1.49; 95% CI: 1.08-2.06). Among dementia subtypes, the risk of AD was increased two-fold in the highest compared to lowest quartile of Lp-PLA(2) mass (adjusted HR:1.98, 95% CI:1.22-3.21). Results were attenuated in models of mixed dementia and VaD. Lp-PLA(2) activity also doubled the risk of mixed dementia in the highest compared to lowest quartile (HR:2.21, 95% CI:1.12-4.373). INTERPRETATION: These data support Lp-PLA(2) as a risk factor for dementia independent of CVD and its risk factors. Further study is required to clarify the role of Lp-PLA(2)-related mechanisms in dementia subtypes.